PAKAIAN ADAT: SUATU TINJAUAN ETIKA KRISTEN TERHADAP NILAI-NILAI KEARIFAN LOKAL ULOS BATAK - Sirait, Hikman; Meriyana; Rahayu, Esti (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
Certain church groups or denominations have recently given rise to movements that oppose or are even hostile to custom or tradition, such as those that oppose ulos giving. Arguments opposing the rejection of Batak ulos are frequently illogical and lack a thorough understanding of this culture. Therefore, the goal of this article is to educate the Batak community by presenting the Christian ethical perspective of the Batak ulos' local wisdom values. This will help to prevent the widespread rejection of the Batak people's usage of ulos as their identity. The research methodology employed in this qualitative study is library research and interviews with several sources. The study's findings demonstrate that, when viewed through the lens of Christian ethics, the local wisdom values found in Batak ulos are not in conflict with one another but rather align with God's word. As a result, this essay can significantly aid in educating Batak people from different religious backgrounds on the importance of local wisdom and how the Bible views these values.